FEATURES OF KYRGYZ WEDDING CEREMONIES IN UZBEKISTAN (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
Based on field materials, this article describes traditional approaches to creating a family and the processes of transformation of wedding rituals and traditions among the Kyrgyz of Uzbekistan at the present stage. The stages of wedding ceremonies are described, the interrelation and mutual influence of Uzbek and Kyrgyz culture and its reflection on the traditions of ethnic Kyrgyz are considered.
Keywords: tradition, matchmaking, wedding, hospitality, groom, redemption, newlyweds, blessing.